How Has Islamic Communication Research Evolved in Indonesia? - Choirin, Muhammad; Sanjaya, Makroen; Chomariah, Lailatul (Institut Agama Islam Sunan Giri Ponorogo, 2026)
This study examines the development of Islamic communication scholarship in Indonesia as reflected in publications within leading Scopus-indexed journals between 2016 and 2024. By employing a bibliometric approach and conducting keyword analysis across eight selected journals, the research maps key trends, publication dynamics, author and institutional contributions, as well as the dominant thematic orientations of the field. The analysis covers publication volume, citation performance, and collaboration networks among scholars. The findings indicate that, although still relatively limited, research output in Islamic communication has steadily increased over the past nine years. Prominent themes include marketing, literacy, business, tourism, banking, and finance, which have emerged as central areas of scholarly attention. The study also identifies a growing pattern of collaboration among authors, both nationally and internationally. Overall, these results provide a comprehensive picture of the trajectory of Islamic communication research in Indonesia, offering important implications for future inquiry, and encouraging greater cooperation and innovation among researchers in this discipline.